Characteristics of Class II division 2 malocclusion and implications in connection with treatment planning - Hille-Padalis, Anna; Williams, Stephen; W. Loster, Bartłomiej (Journal of Stomatology, 2017)
The aim of the present report is to describe the morphology of Class II division 2 malocclusion based on a cephalometric comparison of a group of 48 individuals (Björk). Results demonstrate a clear increase in the sagittal jaw relationship related to a retrognathic mandible, which demonstrates morphology indicative of an anterior rotational growth pattern. In the vertical plane, a skeletal deep bite was seen though the distribution of this anomaly was seen to be dichotomous suggesting that two morphologically different groups could be identified. The role of perioral musculature in the development of the retroclined incisors (maxillary and mandibular) was discussed. As an addendum to the main report a differentiated treatment protocol relating particularly to the vertical jaw relationship was presented and discussed.